2 Subcutaneous Testosterone Enanthate and the Effect of Body Mass Index on Serum Testosterone in Men with Testosterone Deficiency. Issue 1 (1st April 2022) - Miner, M; Amy, T; Gollen, R; Zhou, X; Yan, H; Jaffe, J
ABSTRACT: Introduction: Obesity (body mass index [BMI] ≥30 kg/m^2) in men is associated with low testosterone (T) levels, and the prevalence of testosterone deficiency (TD) is greater in obese men. Information is limited regarding how BMI affects the pharmacokinetic (PK) profile or dosing of testosterone therapies (TTh) in men with TD. Serum total testosterone (TT) trough concentration (C-trough)-guided dosing achieved physiological serum TT levels (300-1100 ng/dL) in a Phase 3 trial of subcutaneous (SC) testosterone enanthate (TE) administered weekly. Objective: This post-hoc analysis evaluated the association between BMI and serum TT to assess PK parameters of weekly SC TE treatment in men with TD and varying BMIs. Methods: Concentration-controlled SC TE was evaluated in a single-arm Phase 3 trial. The primary endpoint was the percentage of patients who received ≥1 dose of SC TE (Safety Population) achieving an average serum TT concentration of 300-1100 ng/dL over the 7-day dosing interval, C-avg (0-168h), at Week 12. The PK Population (n=142) included all patients in the Safety Population with ≥1 blood sample drawn post-dose. Patients in the PK Population who completed the study through Week 12 (n=137) were categorized into tertiles based on baseline BMI: Tertile 1 (BMI ≤29 kg/m^2; n=45), Tertile 2 (BMI >29-32 kg/m^2; n=33), and Tertile 3 (BMI >32 kg/m^2; n=59). Assessed PK parameters included C-trough, AUC-(0-168h), C-avg (0-168h), and C-max. Weeks 6 and 12 C-trough and C-avg (0-168h) were assessed by BMI tertiles. C-trough and C-avg (0-168h) were calculated according to their Week 12 treatment doses, and an overall dose-normalized linear regression model at Week 12 was used. Results: At baseline, mean (SD) serum TT levels for patients in Tertiles 1-3 were 250.7 (101.3), 235.3 (91.2), and 226.4 (81.1) ng/dL, respectively. Prior to dosing adjustments at Week 6, Tertiles 2 and 3 mean (SD) C-trough (459.2 [157.0] and 453.2 [133.0] ng/dL) were lower than Tertile 1 (616.9 [181.6] ng/dL). At Week 6, 21.2% of the total variance in C-trough levels could be predicted from BMI (P<0.001). At Week 12, patients in Tertiles 2 and 3 had lower TT C-trough (494.8 [137.6] and 469.0 [146.2] ng/dL) compared to 517.7 (153.5) ng/dL in Tertile 1. Mean (SD) C-avg (0-168h) values were 585.2 (148.1), 554.2 (104.5), and 528.5 (118.0) ng/dL in Tertiles 1-3, respectively. Mean doses at Week 12 for Tertiles 1-3 were 65.0 (13.48), 78.0 (12.12), and 78.4 (12.68) mg, respectively. Thus, the patients in Tertiles 2 and 3 require higher final doses of SC TE compared to patients in Tertile 1. Using an overall dose-normalized linear regression model at Week 12, 9.36% (P<0.001) and 16.96% (P<0.001) of the total variance in C-trough and C-avg (0-168h), respectively, can be predicted from independent BMI and dose variables. Overall, 98.5% of Week 12 completers achieved C-avg (0-168h) of 300-1100 ng/dL. Conclusions: Week 12 TT C-trough, C-avg (0-168h), and C-max were inversely related to BMI, suggesting an important role for BMI and final dose selection in SC TE exposure. Patients with higher BMI tertiles may require higher testosterone dosing to replete physiologic levels. Disclosure: Yes, this is sponsored by industry/sponsor: Antares Pharma, Inc. Clarification: Industry initiated, executed and funded study Any of the authors act as a consultant, employee or shareholder of an industry for: Antares Pharma, Inc.